Exploring the role of trade facilitation in supporting integrity in trade - Moïsé, Evdokia (OECD Trade Policy Papers, 2019)
Corruption at the border distorts resource allocation, undermines the level playing field for businesses, hampers the attractiveness of affected markets, and may result in significant revenue losses for developing countries. Trade facilitation policies could potentially reduce the incentives and the opportunities for corruption. This paper explores potential determinants of border-related corruption and trade facilitation policies most likely to address it. Countries with higher integrity at the border are found to also have more efficient border processes. Measures that appear to particularly support integrity at the border include transparency and predictability, streamlining of formalities - through simplification of documents, more automation of processes at different levels of complexity, or improved procedures along the border transaction chain - and coordinated border management